Multilevel factors predict medication adherence in rheumatoid arthritis: a 6-month cohort study - Balsa, Alejandro; García de Yébenes, Maria Jesus; Carmona, Loreto; Courel, Laura Garrido; Mendizábal, Javier; Restrepo, Juliana; Fábregas, Dolores; Saenz de Buruaga, Joana Atxotegi; Etxebarrieta, Javier Duruelo; Zavaleta, Nathali Rivas; Carmona, Eugenio Chamizo; Chaves, Lara; et al. (Annals of the rheumatic diseases, 2022)
Non-adherence challenges efficacy and costs of healthcare. Knowledge of the underlying factors is essential to design effective intervention strategies.ObjectivesTo estimate the prevalence of treatment adherence in rheumatoid arthritis (RA) and to evaluate its predictors.MethodsA 6-month prospective cohort study of patients with RA selected by systematic stratified sampling (33% on first disease-modifying rheumatic drug (DMARD), 33% on second-line DMARD and 33% on biologics). The outcome measure was treatment adherence, defined by a score greater than 80% both in the Compliance Questionnaire in Rheumatology and the Reported Adherence to Medication scale, and was estimated with 95% CIs. Predictive factors included sociodemographic, psychological, clinical, drug-related, patient–doctor relationship related and logistic. Their effect on 6-month adherence was examined by multilevel logistic models adjusted for baseline covariates.Results180 patients were recruited (77% women, mean age 60.8). The prevalence of adherence was 59.1% (95% CI 48.1% to 71.8%). Patients on biologics showed higher adherence and perceived a higher medication need than the others; patients on second-line DMARDs had experienced more adverse events than the others. The variables explaining adherence in the final multivariate model were the type of treatment prescribed (second-line DMARDs OR=5.22, and biologics OR=3.76), agreement on treatment (OR=4.57), having received information on treatment adaptation (OR=1.42) and the physician perception of patient trust (OR=1.58). These effects were independent of disease activity.ConclusionTreatment adherence in RA is far from complete. Psychological, communicational and logistic factors influence treatment adherence in RA to a greater extent than sociodemographic or clinical factors.